Teaching Arabic Speaking Skills Based on Sociocultural Theory in Simulation Model: A Case Study of Arabic Language Department Students: تدريس مهارات التحدث باللغة العربية على أساس النظرية السوسيولوجية الثقافية في نموذج المحاكاة: دراسة حالة لطلبة قسم اللغة العربية - M. Imam Zaenal Abidin; Wildana Wargadinata; Ahmad Muballigh (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Arabic speaking skill acquisition in Arabic Language Education (PBA) programs often faces challenges due to the lack of interactive teaching methods aligned with the language's complexity. This study addresses the gap by applying Vygotsky's sociocultural theory, which posits language develops through social interaction. This study addresses the prevalent gap in effective Arabic speaking pedagogy by integrating Vygotsky's sociocultural theory into a simulation-based learning model. It explores how such an approach enhances the speaking skills of students in an Arabic Language Education (PBA) program. Employing a qualitative case study design, the research investigates student experiences and perceptions within this interactive framework. Findings demonstrate a significant improvement in students' Arabic speaking proficiency, accompanied by elevated confidence and motivation. The study concludes that simulation models grounded in sociocultural theory offer a potent pedagogical innovation, contributing valuable insights to the discourse on communicative language teaching and the practical application of social learning paradigms in foreign language education.